A study on the genus Stenus Latreille from Tianmushan Mountain Chain of East China (Coleoptera, Staphylinidae) - Tang, Liang; Puthz, Volker; Yue, Yan-Li (Zootaxa, 2016)
The species of the genus Stenus Latreille from Tianmushan Mountain Chain, North Zhejiang, East China, are reviewed and three new species are described: S. tianmushanus sp. n., S. tonghanggangus sp. n., and S. pseudomicuba sp. n. Diagnostic characters of the new species are illustrated and a key to species of the area is provided.